Acute Middle East Respiratory Syndrome Coronavirus Infection in Livestock Dromedaries, Dubai, 2014 - Wernery, Ulrich; Corman, Victor M.; Wong, Emily Y.M.; Tsang, Alan K.L.; Muth, Doreen; Lau, Susanna K. P.; Khazanehdari, Kamal; Zirkel, Florian; Ali, Mansoor; Nagy, Peter; Juhasz, Jutka; Wernery, Renate; et al. (Emerging infectious diseases, 2015)
Camels carry Middle East respiratory syndrome coronavirus, but little is known about infection age or prevalence. We studied >800 dromedaries of all ages and 15 mother-calf pairs. This syndrome constitutes an acute, epidemic, and time-limited infection in camels <4 years of age, particularly calves. Delayed social separation of calves might reduce human infection risk.